The Genetic Characterization of Grapevine Genetic Resources in Peru Identifies Novel Criolla Varietal Genotypes - Almanza Cano, Aybel (2025)
Today's wine and Pisco grape production in Peru is largely dominated by a reduced number of grapevine (Vitis vinifera L.) varieties. However, Peru is home to a high number of lesser-known local varieties that are still present in traditional vineyards and/or preserved in national or regional grapevine collections, of interest to diversify the local industry. Here, we analyzed 121 grapevine accessions preserved in the ampelographic collection of the Instituto Nacional de Innovación Agraria (INIA-EEA) at Chincha (Ica, Peru), using a combined SNP and SSR genetic profiling strategy for their molecular characterization and identification. This approach led to the differentiation of 45 different grapevine genetic profiles, 40 of them corresponding to already catalogued table and wine grape varieties of diverse geographic origin. Interestingly, we found five grapevines with genetic profiles not registered before. Some of them were found to be descendants of Listán Prieto and/or Muscat of Alexandria, increasing the known role of these two varieties as founders of the Criolla varieties, the autochthonous South American grapevine germplasm. A predominance of the varieties Listán Prieto and Quebranta was also observed, as they were found to be preserved multiple times in the INIA-EEA Grapevine Collection under different local synonyms. Strikingly, the phenotypic description of different accessions matching the genotypes of these two relevant varieties showed a high degree of phenotypic diversity, including the identification of novel berry-color and Muscat-flavored somatic variants that might have a direct impact toward local grape industry diversification. These findings underline the importance of the local genetic resources preserved at the INIA-EEA Grapevine Collection for grapevine improvement. Registering the newly identified varieties and somatic variants with novel traits of interest would represent a crucial first step toward making this plant material available to local grape growers, ultimately promoting the diversification of the Peruvian grape, wine, and Pisco industries.